Penerapan Model Resolusi Konflik Berbantuan Media Kain Perca Untuk Meningkatkan Sikap Menghargai Karya Orang Lain - Oktaviana, Dinda; Rustini, Tin; Hidayah, Nurul; Wahyuningsih, Yona (Universitas Hamzanwadi, 2025)
Arts and Culture and Crafts (SBdP) learning in elementary schools does not only focus on cognitive aspects, but also on developing attitudes and skills. One important attitude that needs to be developed is respecting other people's work. This research aims to analyze and describe the application of a conflict resolution model assisted by patchwork media in increasing attitudes of respect for other people's work in sixth grade elementary school students. The research method used is qualitative with a descriptive approach. Participants in this research were 16 class VI students at SDN Cangkuang 03, Rancaekek District. Data collection techniques are carried out through observation, interviews, questionnaires and documentation. The results of the research show that the application of the patchwork-assisted conflict resolution model provides students with direct experience in working together and understanding the importance of respecting other people's work. This learning process encourages students to actively participate in group discussions, support each other in creating work, and appreciate the work of their friends. This study provides implications for teachers to adopt arts-based approaches and conflict resolution in SBdP learning. In this way, students not only develop creative skills but also build positive values ​​in their social life.